2015
DOI: 10.1111/soru.12105
|View full text |Cite
|
Sign up to set email alerts
|

The Framing of Public Knowledge Controversies in the Media: A Comparative Analysis of the Portrayal of Badger Vaccination in the English National, Regional and Farming Press

Abstract: Science has a powerful role in society. It can fuel innovation, shape policy and influence public opinion. However, science can also be highly controversial and subject to substantial disagreement and debate. Such debates are often evident in the media which regularly reports on areas of disagreement and debate. This article draws on the case-study of bovine tuberculosis (bTB), which has become a highly politicised issue in recent years, to explore media representation of public knowledge controversies. The di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…The multi-dimensional aspects and complexity of the evolution of cattle TB policy in the UK raises many questions on the ethics and value systems of stakeholders in the context of culling of badgers. The role of the media is of key importance in framing the viewpoints of many of the principal actors (85). Where there is difficulty in understanding the complexity of the scientific evidence, the press can influence perspectives by over-simplifying the arguments for or against a particular strategy e.g., culling or vaccination, and this can help to fuel the controversies.…”
Section: Badger Tb In Ireland and The Ukmentioning
confidence: 99%
See 1 more Smart Citation
“…The multi-dimensional aspects and complexity of the evolution of cattle TB policy in the UK raises many questions on the ethics and value systems of stakeholders in the context of culling of badgers. The role of the media is of key importance in framing the viewpoints of many of the principal actors (85). Where there is difficulty in understanding the complexity of the scientific evidence, the press can influence perspectives by over-simplifying the arguments for or against a particular strategy e.g., culling or vaccination, and this can help to fuel the controversies.…”
Section: Badger Tb In Ireland and The Ukmentioning
confidence: 99%
“…Studies of UK farmers' perceptions of vaccination as a means to control TB have also revealed cautious attitudes to this strategy (157). It has been noted that the media paid more attention to vaccination when the controversies over culling escalated (85), and wildlife groups have heavily promoted the vaccine strategy. While there is good field data to show that the vaccine can protect badgers in their natural environment, the scientific evidence of a direct link between badger vaccination and time scales for a positive impact in reducing TB breakdowns in cattle is lacking.…”
Section: Vaccination Of Wildlife Against Tbmentioning
confidence: 99%
“…A number of studies have revealed how certain actors in the debate have framed the bTB control issue. Work has clustered around 1) farmers viewpoints (e.g., Vanclay and Enticott 2011; Maye et al 2014; Robinson 2017a), 2) polarisation of the debate in the media (Cassidy 2012; Naylor et al 2017), among the public (Enticott 2015) and across advocacy coalitions (Lodge and Matkus 2014); and 3) the specific argumentative ecology of the bTB debate on Twitter (Sandover et al 2018) and using Q‐sort analysis (e.g., Price et al 2017).…”
Section: Conflict and The Control Of Bovine Tbmentioning
confidence: 99%
“…Studies that have looked at frames on different sides of the debate have tended to support the notion that they are highly polarised. Naylor et al (2017), for example, look at the ways in which the debate has been framed in the media. Their work reveals three ‘dualistic’ framings that juxtapose: 1) science against the practical reality of modern farming; 2) badger vaccination against badger culling; and 3) victims (farmers and badgers) against culprits (badgers and policy).…”
Section: Conflict and The Control Of Bovine Tbmentioning
confidence: 99%
“…The most reported criminal act to the Badger Persecution Delivery Group is sett disturbance, accounting for 249 (41% of the total) of badger incidents in the UK in 2016 [6]. There is also the current 'good-bad badger paradox' [8][9], where the species is seen as either a 'victim' or a 'culprit'. The Government permit the licensed control of badgers to prevent the spread of bovine tuberculosis (TB), therefore they are regarded as the 'culprit' of disease transmission between wild and farmed animals.…”
Section: Introductionmentioning
confidence: 99%